Prevalence of Atrial Fibrillation and Associated Mortality Among Hospitalized Patients With COVID-19: A Systematic Review and Meta-Analysis - Li, Zuwei; Shao, Wen; Zhang, Jing; Ma, Jianyong; Huang, Shanshan; Yu, Peng; Zhu, Wengen; Liu, Xiao (Frontiers in Cardiovascular Medicine, 2021)
Background: Epidemiological studies have shown that atrial fibrillation (AF) is a potential cardiovascular complication of coronavirus disease 2019 (COVID-19). However, the conclusions drawn from previous studies are not consistent. Therefore, we performed a systematic review and meta-analysis to clarify the prevalence and clinical impact of AF and new-onset AF on COVID-19 patients. Methods: PubMed, Embase, the Cochrane Library, and MedRxiv up to February 27, 2021 were searched to identify studies that reported the prevalence and clinical impact of AF and new-onset AF on COVID-19 patients. The study was registered with the PROSPERO (CRD42021238423). Results: A total of 19 eligible studies were included with 21,653 hospitalized patients. The pooled prevalence of AF was 11% on COVID-19 patients. Older (≥60 years) COVID-19 patients had nearly 2.5 fold higher prevalence of AF compared with young (<60 years) COVID-19 patients (13% vs 5%). Europeans had the highest prevalence of AF (15%)，followed by Americans (11%), Asians (6%), and Africans (2%). The prevalence of AF in severe COVID-19 patients was 6 fold higher than that in non-severe COVID-19 patients (19% vs 3%). Furthermore, AF (crude OR: 2.98, 95% CI: 1.91 to 4.66) (adjusted OR: 1.65, 95% CI: 1.16 to 2.35) and new-onset AF (crude OR: 2.32, 95% CI: 1.60 to 3.37) (adjusted OR: 2.01, 95% CI: 1.12 to 3.62) were significantly associated with an increased risk of all-cause death among COVID-19 patients. Conclusion: AF is quite common among hospitalized patients with COVID-19, in particular among older (≥60 years), North American and European, and severe COVID-19 patients. Moreover, AF and new-onset AF were significantly and independently associated with an increased risk of all-cause mortality among hospitalized COVID-19 patients.